Efficiency gains for thermally coupled solar hydrogen production in extreme cold. Issue 8 (1st July 2021) - Kölbach, Moritz; Rehfeld, Kira; May, Matthias M.
Abstract : We analyse the potential of solar hydrogen production in remote and cold world regions such as Antarctica and quantify the efficiency benefits of thermal coupling. Abstract : Hydrogen produced from water using solar energy constitutes a sustainable alternative to fossil fuels, but solar hydrogen is not yet economically competitive. A major question is whether the approach of coupling photovoltaics via the electricity grid to electrolysis is preferential to higher levels of device integration in 'artificial leaf' designs. Here, we scrutinise the effects of thermally coupled solar water splitting on device efficiencies and catalyst footprint for sub-freezing ambient temperatures of −20 °C. These conditions are found for a significant fraction of the year in many world regions. Using a combination of electrochemical experiments and modelling, we demonstrate that thermal coupling broadens the operating window and significantly reduces the required catalyst loading when compared to electrolysis decoupled from photovoltaics. Efficiency benefits differ qualitatively for dual- and triple-junction solar absorbers, which has implications for the general design of outdoor-located photoelectochemical devices. Similar to high-efficiency photovoltaics that reached technological maturity in space, application cases in polar or alpine climates could support the scale-up of solar hydrogen at the global scale.